Jurnal Pendampingan Pembuatan NIB dan Sertifikasi Halal untuk Pelaku Usaha Mikro Kecil (UMK) di Desa Mekarnangka - Nurhayati, Siti; Syarif, Ahmad; Suryana, Suryana; Paula, Lili (El-Mujtama: Jurnal Pengabdian Masyarakat, 2024)
Low understanding of business actors about the range of trademarks and legality licensing. The dedication carried out in this activity is Micro Small Enterprises (UMK) in Mekarnangka Village which is one of the livelihoods of Mekarnangka Village residents by utilizing agricultural products as processed raw materials. In addition, there are also many other micro small business actors who still have not obtained business permits such as NIB and halal certified, so with the program we have compiled can introduce and increase public understanding of the importance of making NIB and halal certification as the legality of a product. The research method uses a mentoring method, which is carried out through 3 stages, namely, planning, implementation and evaluation. Based on data proven by questionnaires, respondents were 22 MSEs in Mekarnangka Village 100%, consisting of 15 business actors who already have a Business Identification Number (NIB) and 7 business actors who already have a Business Identification Number (NIB) and Halal Certificate.